Employee Performance Influenced by Several Aspects in Assistant Staff in General Administration of North Penajam Paser Regency - didik hadiyatno (Jurnal GeoEkonomi, 2019)
This study aims to examine and analyze the influence of work environment, work discipline, and work motivation on the performance of employees of the General Administration Assistant of the Secretariat of North PenajamPaser Regency. The data was collected by interviewing and distributing questionnaires to 60 Administrative Assistants of Public Administration Division of Sekretariat Daerah Regency of PenajamPaser Utara Regency.The samples used are census sampling techniques and data testing techniques used in this study include instrument test, classical assumption test, multiple linear analysis and hypothesis test. Data analysis in this regression. The results of the analysis show that simultaneously work environment, work discipline and work motivation positive and significant influence on the performance of employees of the General Administration Assistant Secretariat of North PenajamPaserUtara Regency. Results partially Work environment, work discipline and work motivation have a positive and significant effect on performance. In this study, work motivation has a dominant influence on the performance of employees Assistant Field General Administration of the Regional Secretariat of PenajamPaser Utara District